PENGARUH KUALITAS PELAYANAN, INOVASI PELAYANAN DAN KOMPETENSI PEGAWAI TERHADAP KEPUASAN PELAKU USAHA UMKM - Diana, I Nyoman (Jurnal Widya Publika, 2023)
In carrying out the duties and functions of the One-Stop Investment and Integrated Services Office (DPMPTSP) in providing public services, of course, it has an impact on community satisfaction, especially among MSME business actors. Public services basically involve very broad aspects of life. In the life of a state, the government has the function of providing various public services needed by the community, starting with services in the form of regulation or other services in order to meet community needs. The formulation of the problem in this study is how the effects of service quality, service innovation, and employee competence affect the satisfaction of MSME business owners at the Badung Regency One-Stop Capital Investment and Integrated Service Office. The number of samples used in this study was 100, using the random sampling method. Data collection using a Likert-scale questionnaire Data analysis techniques using SEM-PLS The results showed that service quality has a positive and significant effect on the satisfaction of MSME business actors; service innovation has a positive and significant effect on the satisfaction of MSME business actors; and employee competence has a positive and significant effect on the satisfaction of MSME business actors. Service quality, service innovation, and employee competence simultaneously affect the satisfaction of MSME business actors at the Badung Regency One-Stop Investment and Integrated Services Office.